Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11250-009-9337-4
|View full text |Cite
|
Sign up to set email alerts
|

Urea treated maize straw for small-scale dairy systems in the highlands of Central Mexico

Abstract: Maize straw is the main roughage for dairy herds in campesino farms in central Mexico. The objective was to evaluate feeding milking cows on maize straw treated with 40 g/kg DM of urea (A) or untreated straw (B), and 3.0 kg/d of 18% CP concentrate. Twenty-four Holsteins in late lactation from 8 farmers were sorted in two groups: sequence A-B-A or B-A-B; periods were 28 days. Mean daily milk yield for the last two weeks per period, and live-weight and body-condition score every 14 days were used for analysis. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…Economic analysis of milk sales clearly demonstrated that the higher margin over feed was obtained by urea-treated rice straw fed groups compared with untreated rice straw (p<0.01) (Table 5). Similarly, García-Martínez et al (2009) reported that sale price of milk and profit was enhanced by urea treated maize straw.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic analysis of milk sales clearly demonstrated that the higher margin over feed was obtained by urea-treated rice straw fed groups compared with untreated rice straw (p<0.01) (Table 5). Similarly, García-Martínez et al (2009) reported that sale price of milk and profit was enhanced by urea treated maize straw.…”
Section: Resultsmentioning
confidence: 99%
“…Rice straw is abundantly available all year in large quantities in the region (Hue et al, 2008) and when urea treated (5%) rice straw can be used as the only source of roughage in the dry season (Wanapat et al, 2000). Urea treatment is an applicable technique for improving the quality of rice straw (Sanh et al, 2002), in terms of increasing protein content, nutrient digestibility, NH 3 -N concentration, VFA production (particularly propionic acid) and milk production (Hart and Wanapat, 1992; Djibrillou et al, 1998; García-Martínez et al, 2009; Wanapat et al, 2009b). Treatment of rice straw with 5% urea has been used in dairy farms but the cost is relatively high due to the increasing price of urea (Wanapat et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods that optimize the use of low quality forages (Hassan, Nisa, Shahzad, & Sarwar, 2011), such as chemical treatments using urea, which have been used with the aim of improving the nutritional characteristics of forage (Nguyen, Wanapat, Khejornsart, & Kongmun, 2012), allowing the use of a plant harvested at advanced stages of development for use in animal feeding. In addition to the increase in the digestibility and dry matter intake (Nisa, Sarwar, Shahzad, & Hassan, 2007), the crude protein content also increases due to non-protein nitrogen (García-Martínez, Albarrán-Portillo, Castelán-Ortega, Espinoza-Ortega, & Arriaga-Jordán, 2009), caused by ammonia on the structure of the cell wall of the hay (Morais et al, 2017). Forage quality, dose of urea applied, moisture content and treatment duration are the main factors affecting the ammoniation process (Ferreira & Zanine, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Maize fodder can be fed safely at all stages of animal growth without any danger (Garcia‐Martinez et al . ; Malisetty et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa, which can be preserved as hay, haylage or silage, is a widely used forage crop in North America, Europe and elsewhere (Garcia‐Martinez et al . ; Aboagye et al . ).…”
Section: Introductionmentioning
confidence: 99%